INCREASING ONLINE PRODUCT MARKETING LEARNING ACHIEVEMENT IN CREATIVE PRODUCT AND ENTREPRENEURSHIP SUBJECTS TO ACCOUNTING CLASS XII STUDENTS USING PROBLEM BASED LEARNING MODEL AT SMKN 1 BUNGURAN BARAT IN THE 2020 ACADEMIC YEAR - Gusrianto, Rozi (Al'Adzkiya Journal, 2021)
This research was carried out at SMK N 1 Bunguran Barat in Class XII Accounting, where the ability of students for online product marketing material in the eyes of each product course was low. The purpose of this classroom action research research is to find out whether the Problem Based Learning method can improve student learning achievement. The data collection method is daily practice exercises followed by a learning achievement test. The data analysis method is descriptive. The results obtained from this study are group assignment methods with Problem Based Learning Models that can improve student learning achievement. This is evident from the results obtained initially reaching an average value of 48.75, in the first cycle the average value was 67.50 and in the second cycle the average value was 73.88. The conclusion obtained from this study is that the Problem Based Learning learning model through independent and group assignment techniques can improve learning achievement.